การเปลี่ยนปาล์มโอเลอินเป็นเชื้อเพลิงชีวภาพสำหรับอากาศยานบนนิกเกิลที่รองรับด้วยซีโอไลต์ชนิดบีตาและเอชวาย - ธนวัฒน์ สุขอนันต์ (จุฬาลงกรณ์มหาวิทยาลัย, 2019)
The aim of this study is to produce quality jet biofuel with high amount of normal paraffins, branch chain, low aromatic hydrocarbons and low oxygen content from palm olein using Beta and HY zeolites supporting Ni as catalyst in a micro reactor. The experiments were done by varied operating conditions as reactor temperature 360-460 ⁰C, mass of nickel 0-15% by weight, initial hydrogen pressure 0-10 bar and mass of catalyst 0-5% by weight with reaction time 5 hours. From the results, it was found that the reaction temperature, amount of nickel, initial hydrogen pressure and weight of catalyst were significantly affected to the oil yield and product selectivity. The analyst oil product from simulated distillation gas chromatography and gas chromatography-mass spectrometer was found that the reaction temperature is 430⁰C and initial hydrogen pressure 10 bar by using 5%Ni/Beta Zeolite as catalyst for 5 hours. This was optimum condition of thermal cracking, deoxygenation and isomerization that gave the highest yield and quality of bio jet. The oil yield was 63% by weight, 56% bio jet, 28% gasoline, 13% diesel and 3% long residues and the selectivity of oil product was 58% alkane, 23%aromatic and 19% branch chain respectively.